2013
DOI: 10.3390/md11061866
|View full text |Cite
|
Sign up to set email alerts
|

Self-Association of Okadaic Acid: Structural and Pharmacological Significance

Abstract: Okadaic acid (OA) has been an invaluable pharmacological tool in the study of cellular signaling. The great affinity of this polyether for its targets together with its high specificity to inhibit certain protein phosphatases enables the differential study of these proteins. Crystallographic structures of protein phosphatases in complex with OA show a 1:1 protein to toxin ratio. Nevertheless, it has been found that OA is able to self-associate under certain conditions although very little is known about the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In contrast, DTX-3 is inactive against these proteins if not hydrolyzed [ 21 ]. The PP inhibition leads to a dramatic increase of phosphorylation of a number of proteins resulting in important cell alterations, and this is the main reason why OA is an invaluable pharmacological tool in the study of cellular signaling [ 22 ]. In addition, because of this property, it was suspected that this toxin is much more than a simple diarrheic agent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DTX-3 is inactive against these proteins if not hydrolyzed [ 21 ]. The PP inhibition leads to a dramatic increase of phosphorylation of a number of proteins resulting in important cell alterations, and this is the main reason why OA is an invaluable pharmacological tool in the study of cellular signaling [ 22 ]. In addition, because of this property, it was suspected that this toxin is much more than a simple diarrheic agent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PP2A can be activated via oxidative stress such as high ROS generation to participate in many signaling pathways of mammalian cells [42][43][44][45][46][47]. In fact, our mitochondrial fractionation experiment showed that TRIP-Br1 translocation into mitochondria was blocked when cells were treated with okadaic acid, a PP2A specific inhibitor (Figure 3C) [48,49]. Our hypothesis was further tested in U2OS 4.3 osteosarcoma cells, in which TRIP-Br1 expression could be induced by doxycycline [50].…”
Section: Mitochondrial Translocation Of Trip-br1 Via Dephosphorylatio...mentioning
confidence: 75%
“…Recent reports point to modulation of neurotransmitters that regulate intestinal mobility, along with water and electrolyte secretion as the cause of DSP syndrome (Valdiglesias et al, 2013;Louzao et al, 2015). Protein phosphatases modulate cell signaling pathways so their inhibition by OA and DTXs renders them as an important tool in medical and physiological studies (Meštrović and Pavela-Vrančič, 2003;Cruz et al, 2013;Valdiglesias et al, 2013). In addition, chronic exposure to OA can induce cytotoxicity, neurotoxicity, immunotoxicity, embriotoxicity, genotoxicity and cancer promotion as reviewed by Vilariño et al (2018) and Fu et al (2019).…”
Section: Toxic Bioactive Metabolites Frommentioning
confidence: 99%